Studi Karakteristik Stabilitas dan Konstruksi Kapal Berbahan High Density Polyethylene (HDPE) - Kadhafi, Muammar; Sunardi, Sunardi; Triono, Agus; Sari, Wahida Kartika (Jurnal Rekayasa Mesin, 2021)
The development of fishing and marine tourism requires the support of naval architecture, especially in small boat. The use of wood as the main material for shipbuilding has recently become a problem considering the decreasing availability of wood, while the use of fiber is classified as less environmentally friendly because it uses chemical resin and difficult to repair when it breaks and cannot be recycled. The aim of this research is to design the High-Density Polyethylene (HDPE) boat. The design was carried out by using naval architect design software. The stability of boat was calculated by using three loading conditions such as when leaving the port, in the sea and when returning to the port. The International Maritime Organization (IMO) safety criteria was using to evaluation of boat stability where the three loading conditions have met the IMO standard. The construction of HDPE boat was carried out by using DNV rules.